Peta Kekuatan Politik Hasil Pemilu 2009 - Romli, Lili (Jurnal Penelitian Politik, 2009)
The 2009 election has resulted a map ofpolitical change of the election winner The winner of the 2004 election was Golkar Party while in the 2009 election the winner was Democrat Party The 2009 election became a punishment for old parties like Golkar PDIP and PPP since their votes were decreasing sharply compare to previous election Meanwhile two new parties Gerindra and Hanura had successfully entered Senayan parliament by defeating previous parties that had existed in the parliament The Islamic Parties with their Islamic basis mass except PKS has failed to get electoral support due to their decreasing votes or did not pass the electoral threshold This also happened to nationalist parties and christian basis mass parties.